DETERMINAN KEAKTIFAN KADER POSYANDU BALITA - Janah, Esti Nur; Nuryatna, Dedih; Cahyani, Desy Dwi; Situmeang, Lamria (Ensiklopedia of Journal, 2025)
Abstract: Posyandu is one form of community-based health efforts that aims to improve the health status of the community. There are a number of factors that become obstacles in optimizing posyandu services. These obstacles include limited funding sources. The purpose of the study was to determine the determinants of the activeness of posyandu cadres for toddlers. The research design used in this study was cross sectional. The research was conducted in the work area of UPT Puskesmas Sri Padang. The study population was all posyandu cadres in the work area of UPT Puskesmas Sri Padang as well as the research sample which amounted to 40 respondents. The sampling technique used in this study was total sampling. Data analysis was carried out univariate and bivariate. The results showed a relationship between incentives (p value: 0.043) and motivation (p value: 0.009) to the activeness of cadres. It is recommended that the puskesmas further increase promotive efforts when providing training for cadres in increasing knowledge about the tasks and functions of posyandu, always providing appropriate incentives as a form of motivation in increasing the activeness of cadres in posyandu activities.Keywords: Cadres, Motivation, Posyandu.